Changes in Lipid and Hematological Indices among Saudi Patients with Chronic Hepatitis B in the Makkah Region: A Case‒Control Study - Karkashan, Alaa; Alsharif, Dhuha; Batook, Noof; Abbas, Basma; Alsofyani, Abeer (Journal of Contemporary Medical Sciences, 2025)
Objectives: This study investigates hematologic and lipid abnormalities in chronic hepatitis B (CHB) patients to better understand its systemic effects and improve treatment strategies. Methods: We compared 226 CHB patients to an equivalent number of non-HBV individuals between 2015 and 2021 in this retrospective study. Patient data were obtained from the Ministry of National Guard Health Affairs-Western Region (MNGHA-WR) database. Categorical data was analyzed using a chi-square test, while numerical variables were tested using a t-test with a significance threshold of P < 0.05. Age and gender adjustments were made to ensure the comparability of the results. Results: The sex distribution of the CHB and non-HBV groups was comparable (P = 0.51), although non-HBV individuals were significantly older than those with CHB. CHB patients had significantly lower levels of HDL, TC, TG, WBC, RBC, PLT, Hgb, and MCHC, as well as decreased HCT and MCV, compared to non-HBV patients (P < 0.05). These differences persisted statistically significant even after adjusting for age and gender, except for TC and TG levels. Conclusion: This study sheds light on the altered lipid and hematologic profiles of CHB patients as compared to non-HBV individuals. Our findings may help us better understand the extrahepatic consequences associated with CHB and establish an improved medical strategy for these patients.